Inclusive design methods for the development of Mobility Design System for people with disabilities in Malaysia - Ariff, Ahmad Fairuz (2023)
There is a need to incorporating inclusive design methods for the development of mobility design system for people with disabilities (PWDs) in Malaysia, due to lacking on some specific areas in product development stages in cooperating with design philosophy and user study in local. In current, there are many improvements areas which can take place to improve on current wheelchair design especially among Malaysian users and its functionalities which includes its shape, seating position, appearances, safety, ergonomics and cost. Therefore, there is a potential study area to prove that present Mobility Design System (MDS) needs more attention to be systematically develop according to user needs. The aim of this study is to conceptualize Inclusive Design philosophy in product development for People with Disabilities (PWDs) in catering their daily activities. This research adopts the understanding of Inclusive Design theory with Design Development Research (DDR) to understand about user in its design research and product development stages (as in 3 different stages of development in this research). The study has been conducted into a mixed methods data collection phases which involved with interviews, observations and documentations. The data collection stages involved with pilot study activities, main field work including 10 interviews with PWDs, and 5 design expert panels for validations, together with design development process. The process of designs in this research is a process to verify the input collected from the participants during fieldwork. These design process includes the design specifications, and design guidelines to ease the development of a new product for a group of specific users. This research will contribute to the production of a novel framework for researcher, product designer as well as providing a a more understanding about PWDs for a manufacturer and product developer, also to create an opportunity for new product development knowledge. As a consequence of implementing the design process adopting inclusive design framework, the outcome of this research will also be contributing to improve the major issues experienced by PWD when using wheelchairs.